2010
DOI: 10.1002/jcp.22353
|View full text |Cite
|
Sign up to set email alerts
|

Akt/protein kinase B in skeletal muscle physiology and pathology

Abstract: The Akt/protein kinase B is critical regulator of cellular homeostasis with diminished Akt activity being associated with dysregulation of cellular metabolism and cell death while Akt over-activation has been linked to inappropriate cell growth and proliferation. Although the regulation of Akt function has been well characterized in vitro, much less is known regarding the function of Akt in vivo. Here we examine how skeletal muscle Akt expression and enzymatic activity are controlled, the role of Akt in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 99 publications
(208 reference statements)
2
40
0
2
Order By: Relevance
“…Regulation of musclin transcription has been linked to Akt activation (4,6,15,16). Akt is a serine/threonine kinase that has emerged as a critical signaling component for the regulation of cellular metabolism, growth, and survival in multiple systems (17). Akt activity is increased in response to numerous stimuli, including a wide variety of growth factors and hormones activating phosphatidylinositol 3-kinase (PI3-kinase) (18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of musclin transcription has been linked to Akt activation (4,6,15,16). Akt is a serine/threonine kinase that has emerged as a critical signaling component for the regulation of cellular metabolism, growth, and survival in multiple systems (17). Akt activity is increased in response to numerous stimuli, including a wide variety of growth factors and hormones activating phosphatidylinositol 3-kinase (PI3-kinase) (18)(19)(20).…”
Section: Resultsmentioning
confidence: 99%
“…As a statistical significance, results of one-factor ANOVA were used: # p<0.05, ### p<0.001 vs. young rats; *p<0.05, **p<0.01, ***p<0.001 vs. old non-ferulate-fed rats, respectively levels in different aged tissues. For example, both Akt protein levels and activity are generally reduced in insulin-resistant or aged muscle (Wu et al 2011). Another reported that phosphorylation of Akt at Ser 473 and Thr 308 was higher in the soleus muscles of very old rats (33 months) compared with 6-and 27-month-old rats (Wu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the three isoforms are expressed ubiquitously in mammals, their expression level varies depending on the cell type. Akt1 is expressed in all tissues, whereas Akt2 is enriched in insulin-sensitive tissues, such as muscle, adipose tissue and liver (Wu et al, 2011). Akt3 is preferentially expressed in brain, pancreas, lung and kidney.…”
Section: The Complex Relationship Between Notch Wnt and Hypoxiamentioning
confidence: 99%